2015
DOI: 10.2135/cropsci2015.01.0035
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Basis for Glyphosate Tolerance in Hard Fescue and Perennial Ryegrass Cultivars

Abstract: Glyphosate effectively controls susceptible biotypes of numerous weed species, but applications are often injurious to turfgrass. ‘Aurora Gold’ hard fescue (Festuca longifolia Thuill.) and ‘JS‐501’ perennial ryegrass (Lolium perenne L.) have enhanced tolerance to glyphosate compared with traditional varieties, but the mechanisms that convey tolerance are not well understood. The objectives of this research were to investigate the physiological basis for glyphosate tolerance in Aurora Gold hard fescue and JS‐50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Methiozolin, a new experimental herbicide with both pre‐ and postemergence activity on annual bluegrass (Koo et al., 2014), has shown potential to control annual bluegrass on creeping bentgrass putting greens (Brosnan, Calvache, Breeden, & Sorochan, 2013; Brosnan, Henry, Breeden, Cooper, & Serensits, 2013; McCullough, de Barreda, & Yu, 2013; Xiong, Moss, Haguewood, & Koh, 2015); however, fine fescues, especially hard fescue, appear to be less tolerant to methiozolin (Qu et al., 2019). There has been documented glyphosate tolerance in ‘Aurora Gold’ hard fescue, which could provide effective annual bluegrass control programs at low‐input sites (Hart, Derr, Lycan, Rose‐Fricker, & Meyer, 2005; McCullough, Yu, Schilling, & Czarnota, 2015). Askew, Askew, and Goatley (2019) reported all five fine fescue taxa were inherently tolerant of glyphosate at ≤0.7 kg ha −1 rates, with the most to least tolerant in the following order: hard fescue, sheep fescue, strong creeping red fescue, slender creeping red fescue, and Chewings fescue.…”
Section: Management Practicesmentioning
confidence: 99%
“…Methiozolin, a new experimental herbicide with both pre‐ and postemergence activity on annual bluegrass (Koo et al., 2014), has shown potential to control annual bluegrass on creeping bentgrass putting greens (Brosnan, Calvache, Breeden, & Sorochan, 2013; Brosnan, Henry, Breeden, Cooper, & Serensits, 2013; McCullough, de Barreda, & Yu, 2013; Xiong, Moss, Haguewood, & Koh, 2015); however, fine fescues, especially hard fescue, appear to be less tolerant to methiozolin (Qu et al., 2019). There has been documented glyphosate tolerance in ‘Aurora Gold’ hard fescue, which could provide effective annual bluegrass control programs at low‐input sites (Hart, Derr, Lycan, Rose‐Fricker, & Meyer, 2005; McCullough, Yu, Schilling, & Czarnota, 2015). Askew, Askew, and Goatley (2019) reported all five fine fescue taxa were inherently tolerant of glyphosate at ≤0.7 kg ha −1 rates, with the most to least tolerant in the following order: hard fescue, sheep fescue, strong creeping red fescue, slender creeping red fescue, and Chewings fescue.…”
Section: Management Practicesmentioning
confidence: 99%
“…10 The activity of glyphosate varies with its absorption and translocation rate. 29 Other authors working with fomesafen, a herbicide with the same mode of action (inhibition of PPO) as carfentrazone-ethyl, also observed a reduction in the dry mass of shoots from two hybrids of E. urophylla × E. grandis. 30 The tested herbicides may have affected CO 2 assimilation through their effect on disorganization of the thylakoid membranes.…”
Section: Discussionmentioning
confidence: 94%
“…Differences in tolerance to glyphosate have been reported in Eucalyptus genotypes . The activity of glyphosate varies with its absorption and translocation rate . Other authors working with fomesafen, a herbicide with the same mode of action (inhibition of PPO) as carfentrazone‐ethyl, also observed a reduction in the dry mass of shoots from two hybrids of E. urophylla × E. grandis…”
Section: Discussionmentioning
confidence: 95%
“…The foliar mesotrione uptake was determined following a previously described procedure (McCullough et al 2013(McCullough et al , 2015(McCullough et al , 2016Sidhu et al 2014;Yu et al 2015). Before treatment, the second fully expanded leaf on a selected tiller was covered with Parafilm® (Bemis Company, Neenah, WI 54956).…”
Section: Foliar Absorption Of [ 14 C]mesotrionementioning
confidence: 99%
“…In previous research, the differences in herbicide tolerance among cool-season grasses have been frequently associated with foliar uptake and translocation (Lycan and Hart 2006a;Sidhu et al 2014;Wang and Liu 2007;Yu et al 2013Yu et al , 2015. For example, 'JS-501' is a glyphosate-tolerant perennial ryegrass (Lolium perenne L.) cultivar (Hart et al 2005), while 'Manhattan V' is a glyphosate-susceptible cultivar (McCullough et al 2015). In lab experiments, McCullough et al (2015) found that JS-501 absorbed significantly less [ 14 C]glyphosate than Manhattan V and accumu-lated~50% less shikimate.…”
Section: Introductionmentioning
confidence: 99%